In Vitro Studies on the Mechanism of the Antifibrino-lytic Action of E-Aminocaproic Acid (EACA) - Lukasiewicz, Hanna; Niewiarowski, S (Thrombosis and Haemostasis, 1968)
1. It has been found that EACA does not inhibit activation of human plasminogen into plasmin by SK and UK in a concentration of 5 × 10–2 M. The activation of bovine plasminogen by SK and UK is inhibited by this concentration of EACA but not by a lower one.2. EACA in concentrations of 1,5 × 10–1 – 10–4 M does not inhibit casein proteolysis by plasmin. The proteolysis of fibrinogen and fibrin measured by the release of TCA soluble tyrosine is inhibited by EACA in concentrations of 1,5 × 10–1 – 10–2 M.3. The lysis of non-stabilized clots by plasmin measured in a test tube was inhibited by an EACA concentration of 5 × 10–3 – 5 × 10–4 M. The lysis of stabilized clots by plasmin was inhibited by an EACA concentration of 10–5 M.4. On the basis of experimental findings and data given in literature the authors postulate that the mechanism of the antifibrinolytic effects of EACA consists mainly in a modification of plasmin action on fibrin. These effects are dependent on the structure of the fibrin clots.